Tumor Mesenchymal Stem-Like Cell as a Prognostic Marker in Primary Glioblastoma - Seon-Jin Yoon; Jin-Kyoung Shim; Jong Hee Chang; Ju Hyung Moon; Tae-Hoon Roh; Kyoung Su Sung; Ji-Hyun Lee; Eui-Hyun Kim; Sun Ho Kim; Yong-Kil Hong; Su-Jae Lee; Yong-Min Huh; et al. (Stem Cells International)
The isolation from brain tumors of tumor mesenchymal stem-like cells (tMSLCs) suggests that these cells play a role in creating a microenvironment for tumor initiation and progression. The clinical characteristics of patients with primary glioblastoma (pGBM) positive for tMSLCs have not been determined. This study analyzed samples from 82 patients with pGBM who had undergone tumor removal, pathological diagnosis, and isolation of tMSLC from April 2009 to October 2014. Survival, extent of resection, molecular markers, and tMSLC culture results were statistically evaluated. Median overall survival was 18.6 months, 15.0 months in tMSLC-positive patients and 29.5 months in tMSLC-negative patients (P=0.014). Multivariate cox regression model showed isolation of tMSLC (OR = 2.5, 95% CI = 1.1~5.6, P=0.021) showed poor outcome while larger extent of resection (OR = 0.5, 95% CI = 0.2~0.8, P=0.011) has association with better outcome. The presence of tMSLCs isolated from the specimen of pGBM is associated with the survival of patient.